Tineiden als Bestandteil der Nidicolenfauna (Lepidoptera: Tineidae). - Petersen, Günther (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There are summarized the author's observations and dates from literature on Tineids reared from nests of birds, mammals, and Hymenoptera. The results discussed are to show that Tineid species are widely distributed in nests and to induce further investigations especially on the hymenopterous nest fauna, where species of some genera are supposed to be found the life history of which is still unknown. Furthermore there is stressed the role of birds' and hymenopterous nests as a source of domestic pests of the family Tineidae.